44. DETERMINATION OF SPECIES COMPOSITION AND DENSITY OF ANOPHELES MOSQUITOES IN SOME PROVINCES OF SOUTHERN COASTAL AREA, PERIOD 2023 - 2024 (Vietnam Journal of Community Medicine, 2025)
The research results collected 789 Anopheles mosquitoes and 201 Anopheles larvae including 3 species: An. epiroticus, An. nimpe and An. sinensis. Among them, An. epiroticus, the main vector of malaria, dominates with a rate of 94.03% (714/789), followed by An. nimpe accounts for 9.00% (71/789), An. sinensis accounts for the lowest rate of 0.51% (4/789). The species composition of Anopheles in Ca Mau province has been relatively stable over the years.The cross-sectional descriptive study was conducted from January, 2023 to December, 2024 in communes in the southern coastal region to assess the species composition and density of Anopheles mosquitoes in some provinces in the southern coastal region in the period of 2023 – 2024. The results collected 1,520 Anopheles mosquitoes and 442 Anopheles stick beetles including 12 species, an increase of 2 species compared to the period 2019-2023. Only 01 main vector of malaria transmission was detected, An. epiroticus, dominant with a rate of 78.62% (1,195/1,520). The species composition of Anopheles has been relatively stable over the years.At the study sites, the density of An. epiroticus collected by different methods had the highest density from 4.18 to 6.05 mosquitoes /hour/person (for the human screen trap method) and 3.0 mosquitoes /house (for the day indoor scanning method). The density of An. nimpe and An. sinensis collected by different methods was relatively low at the study sites, only from 0.17 to 0.78 mosquitoes /hour/person. Other species such as An. subpictus, An. argyropus, An. peditaeniatus, ... have a negligible density.The density of Anopheles mosquitoes collected by the human curtain trap method has a very high density of 4.7 – 7.98 mosquitoes/person/night, the density of mosquitoes outdoors is 1.70 times higher than the density of mosquitoes in the house. In Ca Mau, the density of An. epiroticus mosquitoes is 3.37 – 39.04 times higher, and the density of Anopheles stick beetles is 2.12 – 2.66 times higher than other research sites in the region.
Keywords: An. epiroticus; mosquitoes; ssspecies composition; species density; southern coastal area